Development of SMART E-Encyclopedia Based on Lepidoptera Diversity in Ndodang Forest as Biology Learning Resource - Utami, Sri; Nuryatman, Pamelia; Dewi, Nurul Kusuma (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to develop a practical and user-friendly SMART E-Encyclopedia of Lepidoptera diversity as a biology learning resource for Class X Students. This research was a Research and Development (R&D) research using the Borg and Gall development model. This research was only carried out for eight stages with the following steps: (a) potential problem, (b). data collection, (c) designing the template on Canva, (d) preparing the draft, (e) uploading the product on the flipbook, (f) validation, (g) revision according to the suggestion of the validator, and (h) uploading the revised product to the flipbook platform. Lepidoptera diversity was identified from March to May 2023 in Ndodang Forest, Widodaren Village, Gerih Sub-district, Ngawi Regency. The development of the SMART E-encyclopedia was conducted from May to August 2023. SMART E-Encyclopedia was subjected to validation by the material expert, media expert, and Class X biology teacher to obtain a score of 70%, 93%, and 80%, respectively. Based on the scores, the product had an average percentage of 81% and was feasible for use as a biology learning resource for Class X students. The advantages of this e-encyclopedia are (1). Explanation of broader material. (2). This E-Encyclopedia was equipped with video and many application features to make it easier for users.